Legal Awareness Program in Cibungur Village, Warungponteng District, Tasikmalaya Regency, West Java, Indonesia - A Ibrahim, Riza; Jaizul W, Alim (International Journal of Humanities, Law, and Politics, 2024)
The people of Cibungur Village, Warungponteng District, Tasikmalaya Regency, West Java, generally have a level of legal awareness that needs improvement, resulting in legal issues. To address the lack of understanding about the law, it is deemed necessary to implement the Keluarga Sadar Hukum (Kadarkum) or Legal Awareness Family Program in an effective and sustainable manner so that the community truly understands the importance of laws that must be followed. This study aims to identify and understand the factors that influence legal awareness, so that the community can comply with the law; and to foster legal awareness within society in accordance with the regulations governing social life in the community. Data and information were obtained through observation, outreach, and interviews. The method used for analyzing the data and information is the normative juridical research method, which integrates existing legal rules with social phenomena in the community by observing the activities of legal awareness families in Cibungur Village, Warungponteng District. The results of the analysis show that community awareness of the law is influenced by several factors, including knowledge, recognition, appreciation, and compliance with the law, which are fundamental aspects.